Different binding and pathogenic effect of neurofascin and contactin–1 autoantibodies in autoimmune nodopathies - Hecker, Katharina; Grüner, Julia; Hartmannsberger, Beate; Appeltshauser, Luise; Villmann, Carmen; Sommer, Claudia; Doppler, Kathrin (Frontiers in Immunology, 2023)
Introduction IgG4 autoantibodies against paranodal proteins are known to induce acute-onset and often severe sensorimotor autoimmune neuropathies. How autoantibodies reach their antigens at the paranode in spite of the myelin barrier is still unclear. Methods We performed in vitro incubation experiments with patient sera on unfixed and unpermeabilized nerve fibers and in vivo intraneural and intrathecal passive transfer of patient IgG to rats, to explore the access of IgG autoantibodies directed against neurofascin-155 and contactin-1 to the paranodes and their pathogenic effect. Results We found that in vitro incubation resulted in weak paranodal binding of anti-contactin-1 autoantibodies whereas anti-neurofascin-155 autoantibodies bound to the nodes more than to the paranodes. After short-term intraneural injection, no nodal or paranodal binding was detectable when using anti-neurofascin-155 antibodies. After repeated intrathecal injections, nodal more than paranodal binding could be detected in animals treated with anti-neurofascin-155, accompanied by sensorimotor neuropathy. In contrast, no paranodal binding was visible in rats intrathecally injected with anti-contactin-1 antibodies, and animals remained unaffected. Conclusion These data support the notion of different pathogenic mechanisms of anti-neurofascin-155 and anti-contactin-1 autoantibodies and different accessibility of paranodal and nodal structures.